Effect of Oil Content and Emulsifier Type on the Properties and Antioxidant Activity of Sea Buckthorn Oil-in-Water Emulsions - Hongxia Zheng; Like Mao; Jingyi Yang; Chenyu Zhang; Song Miao; Yanxiang Gao (Journal of Food Quality)
Sea buckthorn oil-in-water emulsions were prepared through high pressure homogenization, and the effects of droplet size, oil content, and emulsifier type on emulsion properties and the overall antioxidant activity of the emulsions were evaluated. Emulsions with different droplet size were obtained by varying homogenization pressure, and higher oil content resulted in bigger droplet size of the emulsions. Among three tested emulsifiers, sodium caseinate and sugar ester were able to form emulsions with much smaller particle size than soy protein isolate. The emulsions with bigger droplets tended to cream in an accelerated centrifugation test. The antioxidant property of the emulsions was expressed as their DPPH radical scavenging activity. The emulsions processed at lower pressure or contained higher oil content had higher DPPH radical scavenging activity. The soy protein isolate-stabilized emulsion presented higher antioxidant activity than sodium caseinate- and sugar ester-stabilized ones. Upon storage, the antioxidant activity of the emulsions was decreased due to the changes in emulsion stability and the degradation of antioxidants. The knowledge obtained in this study would be useful in developing healthy food containing sea buckthorn oil.